2020
DOI: 10.1002/tesj.542
|View full text |Cite
|
Sign up to set email alerts
|

Job advertisements for English teachers in the Saudi Arabian context: Discourses of discrimination and inequity

Abstract: Recruitment is a form of gatekeeping to the teaching profession, and nonnative-English-speaking teachers' (NNESTs') employability, in particular, has been a major concern for many researchers. In fact, bias favouring native speakers (NSs) without teaching qualifications over nonnative speakers (NNSs) with professional registration has been an acceptable recruitment practice in various contexts. The issue of hiring based on speakerhood in the TESOL profession

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Their conclusions indicated that although academic qualifications and teaching experience were ranked as the two most important requirements, 72% of recruiters were steered by the native speaker criterion when making hiring decisions. Similar findings, documented in Saudi Arabia (Alenazi, 2014;Alshammari, 2021), South America (Mackenzie, 2021), and some Asian countries (Jeon & Lee, 2006), confirmed either explicit or implicit preference of candidates from the anglophone 'Inner Circle' (Kachru, 1986) countries, including the USA, the UK, Canada, Australia, and New Zealand.…”
Section: Inequality Between Nests and Nnests: Defining The Problemsupporting
confidence: 70%
“…Their conclusions indicated that although academic qualifications and teaching experience were ranked as the two most important requirements, 72% of recruiters were steered by the native speaker criterion when making hiring decisions. Similar findings, documented in Saudi Arabia (Alenazi, 2014;Alshammari, 2021), South America (Mackenzie, 2021), and some Asian countries (Jeon & Lee, 2006), confirmed either explicit or implicit preference of candidates from the anglophone 'Inner Circle' (Kachru, 1986) countries, including the USA, the UK, Canada, Australia, and New Zealand.…”
Section: Inequality Between Nests and Nnests: Defining The Problemsupporting
confidence: 70%
“…As we can see from Figure 1, only a vague note is included where the university mentions the government regulations without giving any detail to the prospective candidates. Panos highlighted the discrimination he felt during his recruitment process in the Middle East, which has been validated by Selvi (2010) and Alshammari (2020).…”
Section: Emerging Themesmentioning
confidence: 86%
“…The theoretical discussions on legitimacy and power enacted through the valorization of "standard English" and particular dialects (and their users) and stigmatization of others (and their users) (Lippi-Green, 2012) have real-life consequences for millions of ELT professionals who are un/willingly subjected to this artificial polarity as a category of linguistic (as in NS/NNS) and professional (as in NEST/NNEST) identity. For this reason, employability and recruitment as "a form of gatekeeping to the teaching profession" (Alshammari, 2021), or "the elephant in the room" (Jenkins, 2017, p. 373), has been a prominent focus informing research efforts and advocacy practices in this area. A quick look at the current scholarship reveals several important findings and future directions:…”
Section: Discrimination and Discriminatory Practices In Hiring And Th...mentioning
confidence: 99%
“…The theoretical discussions on legitimacy and power enacted through the valorization of “standard English” and particular dialects (and their users) and stigmatization of others (and their users) (Lippi-Green, 2012) have real-life consequences for millions of ELT professionals who are un/willingly subjected to this artificial polarity as a category of linguistic (as in NS/NNS) and professional (as in NEST/NNEST) identity. For this reason, employability and recruitment as “a form of gatekeeping to the teaching profession” (Alshammari, 2021), or “the elephant in the room” (Jenkins, 2017, p. 373), has been a prominent focus informing research efforts and advocacy practices in this area. A quick look at the current scholarship reveals several important findings and future directions: First and perhaps most disturbingly, despite anti-discrimination laws and the ongoing professional responses (e.g., BC TEAL, 2014; CATESOL, 2013; TESOL, 1992, 2006; TESOL Spain, 2016) proscribing any unfair and unequal treatment based on linguistic and non-linguistic grounds, today, the ELT profession is still characterized by blatant or subtle discrimination and discriminatory practices in hiring processes, salary, and in the workplace.…”
Section: Established Domains Of Inquirymentioning
confidence: 99%
See 1 more Smart Citation